NEXUS BETWEEN ACCOUNTING CONSERVATISM AND BOARD ATTRIBUTES: MODERATING ROLE OF INSTITUTIONAL OWNERSHIP - Saddia Ishfaq , Wajid Alim , Abdul Ghaffar , Saleh Nawaz Khan , Muhammad Sohail , Ammar Ud Din (Migration Letters, 2024)
Accounting conservatism is a principle for preparing financial statements to maintain accuracy and provide an accurate picture of the company’s performance. This study examines the impact of board attributes on accounting conservatism with a moderating role of institutional ownership. Accounting conservatism is treated as a dependent variable, while board attributes (Board independence, Board size, Board diversity) are treated as independent variables in the current study. The current study uses the random effect model for the panel data from 2012-2021 to obtain the main objectives. The study’s findings show that board size and independence are statistically significant and positively related to accounting conservatism. In contrast, board diversity is an insignificant factor in accounting conservatism. Moreover, the study also finds that institutional ownership has an influential role in tackling the issue of accounting conservatism. Institutional ownership with board size and independence has a significant positive association with accounting conservatism in nonfinancial firms. This study breaks new ground by exploring the scarcity of literature on board-specific attributes and institutional investors’ role in addressing accounting conservatism, especially in poorly developed economies. This study significantly adds to the current literature by offering comprehensive insights and empowering investors with valuable information.